THE ANTIBACTERIAL EFFECT OF DIFFERENT PALESTINIAN OAK SPECIES ON MRSA - Renada Shafik Razmaq (My University, 2022)
Introduction: The most common cause of nosocomial pneumonia is staphylococcus aureus, with substantial mortality and morbidity. The growing bacterial resistance and side effects of antimicrobial medications have led to significant attention being paid to traditional medicinal plants in the past few decades. Compounds, derived from these plants, can be used to treat microbial infections as an alternative treatment. Objective: The main aim of this study was to determine the potential antimicrobial effects of ethanol and aqueous extracts of three different species of Quercus against MRSA isolates. Methods: Antibacterial activity of plant extracts was observed, using the agar well diffusion test.After observation, the researcher determined the Minimum Inhibitory Concentration (MIC) by 2-fold dilution of plant extracts yielding a serial dilution of the original extract. To check if the desired compound entered the site of infection in vivo and reached high levels to alter bacterial viability, mice were used as animal models of infection. Results: Ten extractions (water and ethanol) were prepared from the three oak species. However, only seven showed MICs ranging between 1.56-12.5 mg/ml. In vivo testing showed an indication of bacterial inhibition ability of Q.coccifera extract (0.22 mg/ml) when added to the drinking water of a mice group. The bacterial count from a cultured swab from this group of infected mice was 160 CFU, the lowest count of all extracts. Conclusions: Ethanol extracts of oak have more efficient antibacterial activity than water extracts. Water extracts, when mixed with the drinking water of mice, have a good antibacterial inhibitory ability. Future studies should be conducted to extract oak's active ingredients using other solvents. Also, combining these extracts with other antibiotics might enhance their effect in vivo. Keywords: MRSA; Quercus;Palestine; antibiotic resistance; plant extract; MIC;animal model.